IMPLEMENTASI DAN ANALISIS AUGMENTED REALITY (AR) SEBAGAI MEDIA PEMBELAJARAN DI WILAYAH 3T: STUDI KASUS PADA SMA NEGERI 1 ROTE BARAT - Andreas Niko Priyohutomo; Viany Utami Tjhin (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2026)
This study explores the implementation and effectiveness of Augmented Reality (AR) technology as an innovative educational solution for overcoming learning challenges in Indonesia's 3T regions (Tertinggal, Terdepan, dan Terluar - Remote, Frontier, and Underdeveloped areas). Conducted at SMA Negeri 1 Rote Barat, East Nusa Tenggara, this research employs a mixed-methods approach combining qualitative and quantitative data collection through in-depth interviews, classroom observations, student questionnaires (n=60), and documentation analysis over six months (May-October 2025). The study develops a comprehensive research model incorporating Technology Acceptance Model (TAM) variables including Perceived Usefulness, Perceived Ease of Use, Interactivity, Technical Barriers, and Social-Cultural Support as independent variables, with Student Satisfaction as a mediating variable and Continuance Intention as the dependent variable. Results demonstrate that AR implementation significantly enhances student engagement, motivation, and understanding of complex concepts despite infrastructure limitations typical of 3T regions. Social-cultural adaptation and teacher support emerge as critical success factors. The research provides valuable insights for educational policymakers and institutions seeking to implement technology-enhanced learning in underserved areas while addressing unique challenges of remote educational contexts.